Epistemic Responsibility in the Age of Generative Artificial Intelligence: Trust, Authority, and the Ethics of Knowing - Abdi Susanto (Gerakan Indonesia Kita, 2026)
The rapid integration of generative artificial intelligence into knowledge-sensitive domains has prompted extensive ethical debate, largely focused on issues of accuracy, bias, and governance. This article argues that such approaches overlook a more fundamental normative challenge: the transformation of epistemic responsibility and authority in contemporary practices of knowing. Drawing on epistemic ethics and virtue epistemology, the article contends that generative AI systems lack epistemic agency and therefore cannot bear responsibility for knowledge claims. Through normative conceptual analysis, the article identifies a structural